Prevalence of Livestock-Associated MRSA ST398 in a Swine Slaughterhouse in Guangzhou, China - Li, Xiaoshen; Xie, Longfei; Huang, Honghao; Li, Zhi; Li, Guihua; Liu, Peng; Xiao, Danyu; Zhang, Xucai; Xiong, Wenguang; Zeng, Zhenling (Frontiers in Microbiology, 2022)
Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) is an important zoonotic microorganism that is increasingly causing public health concern worldwide. The objective of this study was to determine the transmission and occurrence of MRSA in a slaughterhouse environment and evaluate its antimicrobial resistance and genetic characterization. In this study, we conducted a comprehensive epidemiological survey of S. aureus by spa typing and whole-genome sequencing (WGS) of samples obtained from the pork production chain, the environment, and community residents. To clarify the evolutionary relationships of MRSA sequence type (ST) 398 in this study and global isolates, 197 published whole-genome sequences data of MRSA ST398 strains were downloaded from the GenBank database and included in the phylogenetic analysis. A total of 585 porcine samples (snout and carcass swabs), 78 human nasal samples, and 136 environmental samples were collected. The MRSA isolates were detected at higher frequencies in samples from swine (15.0%) than carcasses (10.0%), slaughterhouse workers (8.0%), community residents (0%), and environment samples (5.9%). The spa typing results showed that t571 accounted for a higher proportion than other spa types. Closely related isolates from the samples of swine, slaughterhouse workers, carcasses, carrier vehicle, and surrounding fishpond water indicate that MRSA ST398 strains may spread among swine, humans, and the environment. MRSA ST398-t571 isolates were genetically different from global strains, except for two Korean isolates, which showed genetic closeness with it. In addition, a MRSA ST398 isolate recovered from an infected patient in Europe differed by only 31 SNPs from the airborne dust-associated strain isolated in this study, thereby suggesting potential transmission among different countries. Antimicrobial susceptibility testing results demonstrated that 99.0% (96/97) of MRSA and 95.1% (231/243) of methicillin-sensitive S. aureus (MSSA) showed multidrug-resistant (MDR) phenotypes. According to WGS analysis, the poxtA-carrying segment (IS431mec-optrA-IS1216-fexB-IS431mec) was reported in MRSA ST398 isolates for the first time. The coexistence of cfr and optrA in a plasmid was first detected in MRSA ST398. The potential transmission of MRSA among humans, animals, and the environment is a cause for concern. The emergence and transmission of LA-MRSA ST398 with high levels of resistance profiles highlight the urgent need for LA-MRSA surveillance.